The implementation of a collaborative peer learning 2:1 model of practice placement education within dietetics pre-registration training in Ireland - Lynam, Ann-Marie (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2021)
The educational approach towards practice education in health-related disciplines has changed in recent years. The use of collaborative peer learning models of practice education has increased, associated with positive effects on desired outcomes such as self-directed (adult) learning, problem-solving skills and reflective practice. These collaborative learning models most frequently consist of a ratio of two students to one educator (2:1). At present, there is little published literature on the impact of collaborative peer learning models on the attainment of professional competence or on the development of professional skills in students during practice education. Furthermore, there is a need for an evidence base for the implementation of this model within the discipline of dietetics. The aim of this study therefore, was to examine the perceived impact of a collaborative peer learning 2:1 model on the attainment of professional competence, the development of professional skills and the overall practice education experience of students and practice educators from an undergraduate dietetics programme. A longitudinal study following a cohort of dietetic students over three years, with data collection at three time points (Timepoints A, B and C) was conducted. A mixed methods research approach was used following a sequential explanatory design, consisting of two separate phases, quantitative followed by qualitative. All students who participated in a 2:1 model were invited to complete a questionnaire at the three time points. Practice educators were invited to complete a questionnaire at the time point at which they facilitated a 2:1 model. The quantitative data were analysed descriptively and inferentially, using non-parametric paired and unpaired comparison tests. Purposeful sampling was undertaken following analysis of the questionnaires at Timepoint B and Timepoint C, in order to identify student and practice educator interviewees with diverse opinions who were then interviewed at the relevant time point. Inductive content analysis, using a thematic approach was used to describe the qualitative data. The response rate for student completion of the questionnaire was high at all three time points, with a final number of 15/16 (93.8%) of those included at Timepoint A remaining at Timepoint C. The response rate for Placement B educator completion of the questionnaire was 25/135 (18.5%) (Timepoint B) and for Placement C educators was 23/134 (17.2%) (Timepoint C). Six students and seven Placement B educators were interviewed at Timepoint B and five students and seven Placement C educators were interviewed at Timepoint C. Students and practice educators reported that a 2:1 model helped students to attain the five professional competencies and develop the six professional skills investigated, during Placement B and the initial stages of Placement C. From the interview data, a number of themes emerged. Careful planning and preparation, and strong practice educator facilitation skills, were found to be essential for successful implementation of a 2:1 model. The 2:1 model was perceived by students and practice educators to be most useful during Placement B and the initial stages of Placement C. Having a peer during practice education was highly regarded both for social and emotional support and to avail of peer learning opportunities. Practice educators perceived that support from colleagues with their caseload may be required in early stages of practice education, but efficiencies were made as students progressed. Students perceived that the time with their peer, independent of the practice educator, was valuable for developing their autonomy. The use of a collaborative peer learning approach within practice education has increased over the past decade and has been associated with many advantages. Despite this, it is not widely used within health-related disciplines, primarily due to perceived challenges to its implementation. This research supports the use of a collaborative peer learning 2:1 model during the early and midway practical components of professional programmes in health-related disciplines, with benefits outweighing any challenges which may need to be overcome. Adequate preparation for students and training for practice educators is essential for the successful implementation of this type of collaborative peer learning 2:1 model.
APPROVED
Keywords: practice placement education; 2:1 model; health related disciplines; dietetics; collaborative learning